EXPERIENCES OF PSYCHOLOGICAL MALTREATMENT IN URBAN MUSLIM UNIVERSITY STUDENTS - Ade Irma Oktiyani; Kiki Nurastriani; Cinthya Fadillah Sari; Nabillah Saputri; Orina Yuliandira; Aisyah Rizky Faradila; Salsabila Rahma Octavia; Rahma Dewi; Putri Andriyani Simanjuntak; Fina Faizatun Nadia; Ugy Alfiansyah; Meirany Khatrine Veronikha; Aloysia Ayfen Senjaya; Daffa Hani Syahirah (CV. Doki Course and Training, 2023)
The purpose of this study is to find out how the experience of psychological persecution occurs in urban students. The type of research used is the survey type. Respondents resulting from the survey totaled 369 respondents who were determined using purposive sampling technique. While the data collection method was carried out by online survey through google form, using the measures of psychological maltreatment questionnaire (PMQ) scale developed by Gokmen Arslan (2017). The data analysis method uses the level categorization test method. The results showed that out of a total of 369 respondents that there were 33 people who tended to experience psychological maltreatment often were women, then 280 people who tended to rarely experience psychological maltreatment were men. From the results of this data, it shows that when viewed from gender, women tend to experience psychological maltreatment more often than men. When viewed from age 21> Years tend to experience psychological maltreatment more often. Age 19-20 years tends to rarely experience psychological maltreatment. Age 17-18 years tends to never experience psychological maltreatment.